Study of Transportasi Mode Selection to Khairun University Campus with Binary Logit Method - Raudha Hakim; Nurmaiyasa Marsaoly; Muhammad Arby Somadayo (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Land transportation mode is the main means of transportation to reach campus II Unkhair Gambesi which can be accessed using motorbikes and public transportation. Ternate City is one of the cities in North Maluku Province which has many important activities in the fields of education, politics, and economy. In addition, the center of government of North Maluku province is also still in the Ternate City area, so it also has an impact on the development of the lives of the people of Ternate City. This study aims to determine the effect of cost and travel time on the selection of transportation modes between private vehicles (motorcycles) and public transportation using the state preference method. This study uses the Stated preference method used for an approach by using respondents’ opinions on various alternative options on the attributes of travel costs and travel time to transportation modes Private Vehicles (Motorcycles) and Public Transportation Case Study: Central Ternate – Campus II Unkhair Gambesi. The results of this study used linear regression analysis and the binary logit method. And it can be concluded that the chance of choosing a Private Vehicle (Motorcycle) is 74% while the chance of choosing public transportation is 26%.